PENGARUH BEBERAPA DOSIS LIMBAH PADAT PABRIK KELAPA SAWIT (SLUDGE) TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA. - Suciati, Rini; saputra, Sukemi indra; ', Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to obtain the best sludge dose for growth of oil palm seeds in main nursery. Research was conducted in the field of Technical Implementation Unit (UPT) experimental garden Faculty of Agriculture, University of Riau, from April to August 2014. The research was carried out experimentsaly using Completely Randomized Design (CRD), consists of 5 treatments and 4 replications, then obtain 20 experimental units. Each experimental unit consist of 3 seeds so that there are 60 seeds. Two seeds each experimental unit were sampled. Each treatment without sludge, sludge at a dose of 40 g/polybag equivalent to 10 tonnes/ha, sludge at a dose of 80 g/polybag equivalent to 20 tonnes/ha, sludge at a dose of 120 g/polybag equivalent to 30 tonnes/ha and sludge with a dose of 160 g/polybag equivalent to 40 tonnes/ha. Parameters measured were the increase of seed height, increase of stump diameter, number of leaf sheaths, roots and seed crown ratio dry stools. Data were analyzed statistically using analysis of variance (ANOVA). Analysis of variance result followed by Duncan test at 5% level. The results shows giving some doses of sludge in the oil palm seedlings significant effect on increase of seed height, increase of stump diameter, roots crown ratio and seeds dry weight, but not significant effected on increase of leaf midrib. Giving sludge 120 g/polybag and 160 g/polybag gave the best results for all parameters compared with other treatments. Keywords: Sludge, oil palm, main nursery